Genome-wide analysis of fatty acid desaturase genes in moso bamboo (Phyllostachys edulis) reveal their important roles in abiotic stresses responses - Chun Fu; Qinchao Fu; Shanshan Wang; Fangzhou Wu; Na Jiang; Ruoqi Zhou; Yaojun Yang; Yufei Xue (BMC Genomics)
Abstract Background Bamboo is an important nontimber forestry product worldwide, while growth, development and geographic distribution of bamboo are often affected by abiotic stresses. Fatty acid desaturases have important roles in regulating plant abiotic stress tolerance, especially low-temperature. However, there is no report on genome-wide of FAD genes in bamboo under abiotic stresses. Results A toltal of 43 PeFAD genes were identified in moso bamboo genome, which were unevenly located in 17 scaffolds. Phylogenetic analysis indicated that PeFAD genes were divided into 6 groups and ADS/FAD5 group was absence in momo bamboo, and gene structure and histidine-motifs remained highly conserved in each group. The expansion of PeFAD genes was mainly caused by tandem and segmental duplications of SAD/FAB2 group. We also identified 59 types of miRNAs targeting PeFAD genes. RNA-seq data indicated that PeFAD genes were transcribed in various organs/tissues with different degrees, and responded to abiotic stresses and hormone treatments, including cold, salt, drought, SA, ABA, BR, NAA and GA. Co-expression analysis under cold stress showed that PeCBF3 might directly bind the promoter of top cold-responsive PeSLD1 gene that contained LTR cis-element and DRE core element. The qRT-PCR assay also validated the expression pattern of PeSLD1 and its upstream regulatory gene PeCBF3. Conclusion In this study, we performed comprehensive genome-wide survey of PeFAD genes in moso bamboo and analyzed their expression patterns in various tissues and organs, and under abiotic stresses and phytohormones treatment. The qRT-PCR assay validated the cold inducibility of PeSLD1 and PeCBF3. This work showed critical roles of PeFAD genes in abiotic stresses responses. This is the first report on genome-wide analysis of PeFAD genes in moso bamboo, which will provide critical gene resources for molecular breeding of stress-toleranct moso bamboo.